Protein ingestion acutely inhibits insulin-stimulated muscle carnitine uptake in healthy young men - Shannon, Chris E.; Nixon, Aline Victoria; Greenhaff, Paul L.; Stephens, Francis B. (American Society for Nutrition, 2016)
BACKGROUND: Increasing skeletal muscle carnitine content represents an appealing intervention in conditions of perturbed lipid metabolism such as obesity and type 2 diabetes but requires chronic L-carnitine feeding on a daily basis in a high-carbohydrate beverage. OBJECTIVE: We investigated whether whey protein ingestion could reduce the carbohydrate load required to stimulate insulin-mediated muscle carnitine accretion. DESIGN: Seven healthy men [mean ± SD age: 24 ± 5 y; body mass index (in kg/m(2)): 23 ± 3] ingested 80 g carbohydrate, 40 g carbohydrate + 40 g protein, or control (flavored water) beverages 60 min after the ingestion of 4.5 g L-carnitine tartrate (3 g L-carnitine; 0.1% (2)[H]3-L-carnitine). Serum insulin concentration, net forearm carnitine balance (NCB; arterialized-venous and venous plasma carnitine difference × brachial artery flow), and carnitine disappearance (Rd) and appearance (Ra) rates were determined at 20-min intervals for 180 min. RESULTS: Serum insulin and plasma flow areas under the curve (AUCs) were similarly elevated by carbohydrate [4.5 ± 0.8 U/L · min (P < 0.01) and 0.5 ± 0.6 L (P < 0.05), respectively] and carbohydrate+protein [3.8 ± 0.6 U/L · min (P < 0.01) and 0.4 ± 0.6 L (P = 0.05), respectively] consumption, respectively, compared with the control visit (0.04 ± 0.1 U/L · min and -0.5 ± 0.2 L). Plasma carnitine AUC was greater after carbohydrate+protein consumption (3.5 ± 0.5 mmol/L · min) than after control and carbohydrate visits [2.1 ± 0.2 mmol/L · min (P < 0.05) and 1.9 ± 0.3 mmol/L · min (P < 0.01), respectively]. NCB AUC with carbohydrate (4.1 ± 3.1 μmol) was greater than during control and carbohydrate-protein visits (-8.6 ± 3.0 and -14.6 ± 6.4 μmol, respectively; P < 0.05), as was Rd AUC after carbohydrate (35.7 ± 25.2 μmol) compared with control and carbohydrate consumption [19.7 ± 15.5 μmol (P = 0.07) and 14.8 ± 9.6 μmol (P < 0.05), respectively]. CONCLUSIONS: The insulin-mediated increase in forearm carnitine balance with carbohydrate consumption was acutely blunted by a carbohydrate+protein beverage, which suggests that carbohydrate+protein could inhibit chronic muscle carnitine accumulation.